2004
DOI: 10.1002/jca.20001
|View full text |Cite
|
Sign up to set email alerts
|

Improved treatment of sudden hearing loss by specific fibrinogen aphaeresis

Abstract: The etiology of sudden sensorineural hearing loss is still unclear and is thought to result from disturbances of microcirculation, infectious causes, or autoimmune disorders. So far standard therapy did not show clear improvement over spontaneous remission rate, which is assumed to be about 50% [Nakashima et al., Acta. Otolaryngol. Stockh. 514:14-16, 1994; Schuknecht and Donovan, Arch. Otorhinolaryngol. 243:1-15, 1986; Harris and Sharp, Laryngoscope 100:516-524, 1990; Mayot et al., Clin. Immunol. Immunopath. 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…The reason why border-zone infarcts occur in cases with major arterial occlusion may be that a hypoperfusion status, caused by slow blood flow, is unable to wash out small emboli that would disappear under normal cerebral perfusion [12]. Based on this observation, slow cochlear blood flow that is highly susceptible to blood pressure fluctuations and impairments in blood flow may play an important role in embolisms of the internal auditory artery [13]. When small emboli stray into the internal auditory artery, sudden death may result from an embolism that should have been washed out in other cerebral vessels under normal perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why border-zone infarcts occur in cases with major arterial occlusion may be that a hypoperfusion status, caused by slow blood flow, is unable to wash out small emboli that would disappear under normal cerebral perfusion [12]. Based on this observation, slow cochlear blood flow that is highly susceptible to blood pressure fluctuations and impairments in blood flow may play an important role in embolisms of the internal auditory artery [13]. When small emboli stray into the internal auditory artery, sudden death may result from an embolism that should have been washed out in other cerebral vessels under normal perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…When small emboli stray into the internal auditory artery, sudden death may result from an embolism that should have been washed out in other cerebral vessels under normal perfusion. Indeed, specific fibrinogen and low-density lipoprotein apheresis techniques have been attempted to improve whole blood and plasma viscosity, and to increase the release of nitric oxide to improve blood flow by vasodilatation [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Many risk factors have been investigated, particularly cardiovascular ones such as diabetes, smoking, increased blood viscosity, elevated fibrinogen, triglycerides, LDL, total cholesterol and several mutations including the glycoprotein la [Ohinata et al, 1994;Suckfüll et al, 2002;Ullrich et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…All 20 apheresis patients improved during immunoadsorption; 60% of patients' auditory thresholds returned to normal after the first immunoadsorption and treatment could be discontinued, while complete recovery was reached after 4 weeks in another 20% of patients. Both these studies demonstrated significantly lowered levels of fibrinogen, and fibrinogen and cholesterol, respectively, after apheresis [20,21]. Valbonesi et al [9] conducted another uncontrolled trial, treating 60 ISHL patients with Rheopheresis (cascade filtration).…”
Section: Apheresismentioning
confidence: 95%
“…Within the HELP group, patients with high levels of fibrinogen seemed to benefit more. Ullrich et al [21] conducted an uncontrolled trial, using fibrinogen apheresis to treat 20 ISHL patients of whom 80% recovered fully under apheresis. Fibrinogen apheresis is a highly specific immunoadsorption, extracting only fibrinogen.…”
Section: Apheresismentioning
confidence: 99%